Development of formaldehyde detector in salted-fish using color sensor - Endi Permata; Yus Rama Denny; Irvan Akram (Universitas Sultan Ageng Tirtayasa, 2021)
Currently, almost all traders use dangerous preservatives in salted fish, one of which is formaldehyde. Traders use these chemicals to make food more durable, even though the food will be consumed by humans. This is due to a lack of knowledge about foods that contain dangerous chemicals. Therefore, the Arduino Uno R3-based tool was developed. This Arduino Uno R3-microcontroller tool can test food practically and effectively quantitatively because it does not take long to see results. The TCS3200 was color sensor is used to detect food samples containing formaldehyde after being mixed with Formaldehyde Main Reagent according to the dosage. The sensor detects the changing color after everything has reacted, and a buzzer alarm will sound when the salted fish has formaldehyde. The test results are displayed on the 16x2 LCD screen and the NetBeans java application, where the output is a detection of whether salted fish has formalin or is formalin free. The initial data collection used a literature study and observation. This study used quantitative analysis and qualitative analysis. Based on the results, the performance test data of Formaldehyde Detector Prototype in Salted Fish Using Arduino Microcontroller-Based TCS3200 Color Sensor obtained a score of 74 or in the